2010
DOI: 10.2503/jjshs1.79.103
|View full text |Cite
|
Sign up to set email alerts
|

Acylated Cyanidin 3-sophoroside-5-glucosides from the Purple Roots of Red Radish (Raphanus sativus L.) ‘Benikanmi’

Abstract: Four new acylated cyanidin glycosides were isolated from the purple root peers of Raphanus sativus L. 'Benikanmi', along with five known anthocyanins. These pigments were based on cyanidin 3-sophoroside-5-glucoside, and acylated diversely with malonic, p-coumaric, caffeic, and ferulic acids. Two pigments of these four new anthocyanins were determined to be cyanidin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…The quantification of anthocyanins including pelargonidin, cyanidin, and delphinidin was investigated by Hanlon and Barnes [4], and many research groups [12,53] also found that the major anthocyanins in radish sprouts are acylated pelargonidins, such as in the Daikon cultivar [54], while other researchers showed that cyanidin-based pigments could be isolated from red radish ( R. sativus L. var. Benikanmi) [55], radish cultivar Sango sprouts [56], and Purple Bordeaux radish [57]. However, other studies have shown that glucoraphasatin purified from radish sprouts has some antioxidant capacity [58], which contributed to the total antioxidant capacity of radish sprout extract [59].…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of anthocyanins including pelargonidin, cyanidin, and delphinidin was investigated by Hanlon and Barnes [4], and many research groups [12,53] also found that the major anthocyanins in radish sprouts are acylated pelargonidins, such as in the Daikon cultivar [54], while other researchers showed that cyanidin-based pigments could be isolated from red radish ( R. sativus L. var. Benikanmi) [55], radish cultivar Sango sprouts [56], and Purple Bordeaux radish [57]. However, other studies have shown that glucoraphasatin purified from radish sprouts has some antioxidant capacity [58], which contributed to the total antioxidant capacity of radish sprout extract [59].…”
Section: Resultsmentioning
confidence: 99%
“…By application of its NOESY experiment, NOEs between H-1 of Glc A and H-4 ( H 8.77) of cyanidin, H-1 of Glc B and H-6 ( H 6.93) of cyanidin, and H-2 ( H 4.12) of Glc A and H-1 of Glc C were observed (Figure 1), supporting glycosylation of the C-3 and C-5 cyanidin hydroxyl groups with Glc A and Glc B, respectively, while also indicating a sophorose structure between Glc A and Glc C. , which is a new anthocyanin in plants [5][6][7][8][9][10][11][12][13][14][15][16][17]. This structure was also confirmed by analysis of its 13 C, 1 H- 13 C HMQC and 1 H-13 C HMBC NMR spectra.…”
Section: Pigmentmentioning
confidence: 86%
“…Hanlon and Barnes (2011) showed a quantification of anthocyanins by classes (pelargonidin, cyanidin and (7) 271 (8) 1035 991 (7) 787 (43) 535 (100) 491 (10) 287 (11) 287 (100) (Giusti & Wrolstad, 2003;Park et al, 2013;Wu & Prior, 2005) also found that the major anthocyanins in radish sprouts are acylated pelargonidins, such as Daikon cultivar (De Nicola et al, 2013), while others reported the isolation of cyanidin-based pigments in red radish (R. sativus L. var. Benikanmi) (Tatsuzawa et al, 2010), Purple Bordeaux radish (Lin, Sun, Chen, & Harnly, 2011) and radish cv. Sango sprouts (Matera et al, 2012).…”
Section: Qualitative and Quantitative Analysis Of Anthocyaninsmentioning
confidence: 99%